Prophylactic Swallowing Exercises in Patients with Laryngeal Cancer Who Underwent Total Laryngectomy—A Randomized Trial - Elena Teodora Schipor-Diaconu; Raluca Grigore; Paula Luiza Bejenaru; Catrinel Beatrice Simion-Antonie; Bianca Petra Taher; Simona Andreea Rujan; Anca Ionela Cirstea; Raluca Andreea Iftimie; Ruxandra Ioana Stancalie-Nedelcu (Current Oncology)
Objectives: This study aims to determine the efficacy of prophylactic swallowing exercises on swallowing function in patients undergoing total laryngectomy for laryngeal cancer. Methods: The design was a randomized controlled trial set in one tertiary care academic medical center. A total of 92 patients undergoing total laryngectomy for stages III and IV laryngeal cancer performed five targeted swallowing exercises for a period of three months after their surgery, starting two weeks after the surgery. Weekly swallowing therapy sessions were held with the patients in order to encourage adherence and proper technique. The controls received no preventive exercise and were referred for swallowing treatment following the surgery, as well as radiation therapy if necessary. The Functional Oral Intake Scale (FOIS) and the Performance Status Scale for Head and Neck Cancer Patients (PSS-H&N) were used to measure swallowing function at the baseline, one week following the surgery, and three, six, nine, and twelve months following the surgery. Results: Right after the surgery, there were no statistically significant variations between the intervention and control groups in the FOIS scores (p value = 0.64), the Eating in Public subscale scores (p value = 1) and Normalcy of Diet subscale scores (p = 0.33) of the PSS-H&N. The scores were significantly better among the intervention patients at months 3, 6, 9, and 12 for all the scores, with p values smaller than 0.000. Conclusions: Although not immediately following the surgery, the patients who engaged in prophylactic swallowing exercises showed improvements in their ability to swallow at 3, 6, 9, and 12 months following their procedure.